Hubungan Budaya Organisasi dan Komunikasi terhadap Efektivitas Kerja melalui Kepuasan Kerja pada Yamaha Tjahaja Baru Kota Solok - Crefioza, Omia; Tasnim, M. (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2025)
This study examines the impact of organizational culture and communication on work effectiveness mediated by job satisfaction at Yamaha Tjahaja Baru Kota Solok. Using Structural Equation Modeling (SEM), data were collected from all 40 employees as the study's population. Results revealed that organizational culture and communication significantly and positively influence both job satisfaction and work effectiveness. However, job satisfaction does not mediate the effect of communication or discipline on work performance. These findings highlight the importance of fostering a strong organizational culture and effective communication to enhance employee performance and organizational outcomes. This research provides actionable recommendations for improving employee satisfaction and productivity, ensuring Yamaha's competitive advantage in the automotive industry.